Redundant data minimisation using hexagonal scalar premier neighbourhood for optimum camera actuation scheme. Issue 3 (16th March 2016) - Priyadarshini, Sushree Bibhuprada B.; Panigrahi, Suvasini
Abstract : This study reports an efficient scheme inspired by scalar premier (SP) selection for actuation of optimum number of cameras so as to minimise the amount of redundant data transmission. The proposed algorithm passes through three major steps. Initially, all the sensors are randomly deployed and messages are exchanged among themselves to know the location information of each other. In the second step, the entire monitored region is divided into number of virtual sub‐regions, in which the scalars present at each sub‐region select six SPs in a hexagonal manner in such a way that the cameras to be activated due to them cover distinct portions of geographic regions. Finally, when event takes place, these SPs communicate their respective cameras regarding its occurrence. Consequently, the cameras exchange messages among each other for deciding which among them are to be actuated. The less camera actuation, improved coverage ratio, reduced event‐loss ratio, least redundancy ratio along with minimised energy and power consumption obtained from the experimental evaluation reveal the effectiveness of the proposed algorithm as compared with two other recently devised approaches in the literature.